KONTRIBUSI DUKUNGAN ORANG TUA DAN KEDISIPLINAN SISWA TERHADAP KREATIVITAS BELAJAR MATEMATIKA KELAS V SD - Ali - Muckromin; Sutama - -; Markhamah - - (JKPD (Jurnal Kajian Pendidikan Dasar), 2022)
This is a new author guidelines and article template of Tematik : journal since year 2016 publication. Article should be started by Title of Article followed by Authors Name and Affiliation Address and abstract. This abstract section should be typed in Italic font and font size of 11 pt and number of words of 150-250. Special for the abstract section, please use left margin of 25 mm, top margin of 30 mm, right and bottom margins of 20 mm. The single spacing should be used between lines in this article. If article is written in Indonesian, the abstract should be typed in Indonesian and English. Meanwhile, if article is written in English, the abstract should be typed in English only. The Abstract is a miniature contents of the entire writing statement, comprise : problem, purpose, method, scientific finding results, and short conclusion. The abstract should only be typed in one paragraph and one-column format.